O rir dos Gregos - Brandão, Jacyntho Lins (2023)
The ambivalence of this paper’s title seeks to highlight the double purpose underlying its approach: not only have we focussed on some of the several categories of Greek laughter, but we have mainly concentrated on why and in what situations the Greeks have laughed at themselves. We have therefore taken into account the written records handed down to us, bearing in mind at all times that the Greeks’ laughter wasn’t confined to specific genres, such as comedy or satire, but it rather emerged even within the context of literary works regarded as “serious”.